Clinical utility of amyloid PET imaging with (18)F-florbetapir: a retrospective study of 100 patients. Issue 3 (10th October 2017) - Carswell, Christopher James; Win, Zarni; Muckle, Kirsty; Kennedy, Angus; Waldman, Adam; Dawe, Gemma; Barwick, Tara D; Khan, Sameer; Malhotra, Paresh A; Perry, Richard J
Abstract : Background and objective: Amyloid-positron emission tomography (PET) imaging (API) detects amyloid-beta pathology early in the course of Alzheimer's disease (AD) with high sensitivity and specificity. (18)F-florbetapir (Amyvid) is an amyloid-binding PET ligand with a half-life suitable for clinical use outside of the research setting. How API affects patient investigation and management in the 'real-world' arena is unknown. To address this, we retrospectively documented the effect of API in patients in the memory clinic. Methods: We reviewed the presenting clinical features, the pre-API and post-API investigations, diagnosis and outcomes for the first 100 patients who had API as part of their routine work-up at the Imperial Memory Centre, a tertiary referral clinic in the UK National Health Service. Results: API was primarily used to investigate patients with atypical clinical features (56 cases) or those that were young at onset (42 cases). MRI features of AD did not always predict positive API (67%), and 6 of 23 patients with MRIs reported as normal were amyloid-PET positive. There were significantly more cases categorised as non-AD dementia post-API (from 11 to 23). Patients investigated when API was initially available had fewer overall investigations and all patients had significantly fewer investigations in total post-API. Conclusions: API has a clear impact on the investigation of young-onset or complex dementia while reducing the overall burden of investigations. It was most useful in younger patients, atypical presentations or individuals with multiple possible causes of cognitive impairment.